Ischemia preconditioning is neuroprotective in a rat cerebral ischemic injury model through autophagy activation and apoptosis inhibition - Xia,D.Y. (2013)
Sublethal ischemic preconditioning (IPC) is a powerful inducer of ischemic brain tolerance. However, its underlying mechanisms are still not well understood. In this study, we chose four different IPC paradigms, namely 5 min (5 min duration), 5×5 min (5 min duration, 2 episodes, 15-min interval), 5×5×5 min (5 min duration, 3 episodes, 15-min intervals), and 15 min (15 min duration), and demonstrated that three episodes of 5 min IPC activated autophagy to the greatest extent 24 h after IPC, as evidenced by Beclin expression and LC3-I/II conversion. Autophagic activation was mediated by the tuberous sclerosis type 1 (TSC1)-mTor signal pathway as IPC increased TSC1 but decreased mTor phosphorylation. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and hematoxylin and eosin staining confirmed that IPC protected against cerebral ischemic/reperfusion (I/R) injury. Critically, 3-methyladenine, an inhibitor of autophagy, abolished the neuroprotection of IPC and, by contrast, rapamycin, an autophagy inducer, potentiated it. Cleaved caspase-3 expression, neurological scores, and infarct volume in different groups further confirmed the protection of IPC against I/R injury. Taken together, our data indicate that autophagy activation might underlie the protection of IPC against ischemic injury by inhibiting apoptosis.